Pengaruh Modal Sosial Terhadap Kinerja Anggota Lembaga Kemasyarakatan Di Kelurahan Beringin Yang Dimediasi Knowledge Sharing - Pujiastuti, Puput; Kistyanto, Anang; Wijayanti W, Dewie Tri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Subdistrict community institutions are a medium for citizen participation as colleagues of the Village Head, who participate in planning, implementing and supervising development, as well as improving the quality of citizen services in the Subdistrict. Therefore, members of community institutions who have skills and knowledge are needed. This research aims to analyze the influence of social capital with network indicators, norms and trust, on the performance of members of Beringin Village community institutions mediated by knowledge sharing. The respondents in this quantitative research were 82 members of Beringin Village community institutions and were analyzed using SmartPLS. The results of the research show that the influence of social capital on knowledge sharing has a p-value of 0.000 < 0.050 so it has a positive and significant influence. The influence of social capital on member performance has a p-value of 0.000 < 0.050, so it can be concluded that it has a positive and significant influence. The influence of knowledge sharing on member performance has a p-value of 0.801 > 0.050, so it can be concluded that knowledge sharing has no effect on member performance. The influence of social capital on performance through knowledge sharing has a p-value of 0.803 > 0.050, so it can be concluded that knowledge sharing does not mediate the influence of social capital on member performance.